21st‐Century Literacies, Critical Media Pedagogies, and Language Arts. (28th November 2012) - Morrell, Ernest
Abstract: In the second decade of the 21st century, information has been globalized, digitized, and sped up to move at the speed of thought. Being literate in this new world means programming personal websites, sending e‐mails from mobile devices and spending hours communicating via virtual social networks. Our students are products of this world. However, for all their digital expertise, there is still a great deal that these youth have to learn about how to process the information they are inundated with via these new portals of information. Teachers today have a responsibility to help students acquire these 21st century literacies without abandoning a commitment to the traditional literacies that have defined education to date. This article argues that language arts educators must inject the discipline with these new tools and ways of communication as concepts such as reading, writing, listening, and speaking take on new dimensions in the media age.